Formative Assessment and Achievement of Mathematics Students in Community Schools of Nepal - Dahal, Bibek (Social Inquiry: Journal of Social Science Research, 2019)
Formative assessment is one of the leading elements of every classroom instruction for making learning contextual and students centred. The formative assessment creates such space where a teacher as adult supporter plays the role of scaffolding on the learning performance of their students. I studied the formative assessment and students' achievement status in mathematics through survey research design. I used the contingency questionnaire as research tool under quantitative research approach. The study was conducted within the target population; total number of community schools and their mathematics students (i.e. 547) who have participated in District Level Examination in 2014. I employed simple random sampling procedure to select the sample respondents (i.e. 232). The contingency questionnaire for students with 0.74 value of internal consistency was used as a research tool to collect the basic information for the study. Regarding the theoretical framework, I used Tomlinson's Differentiated Classroom Instruction and Assessment: Philosophy of Differentiation. The research depicts that regularity of teachers' responses (check) or feedback on the students' classwork, homework, project work and tests have a creditable role in improving their students’ learning performance. Furthermore, project work, a form of formative assessment, helps to improve students’ learning performance through creating an opportunity for learning by doing, which also contributes to contextualize the abstract concept of mathematics.